EFFICACY OF THE SUPRAMOLECULAR COMPLEX OF FENBENDAZOLE AGAINST NEMATODIASIS IN SHEEP - A. I. Varlamova; Yu. V. Limova; K. M. Sadov; A. K. Sadova; E. E. Belova; A. V. Radionov; S. S. Halikov; Yu. S. Chistyachenko; A. V. Dushkin; V. N. Skira; I. A. Arkhipov (Российский паразитологический журнал)
Objective of research: to study the anthelmintic efficacy of the supramolecular complex of Fenbendazole used against different nematode species in sheep Materials and methods: Experiments were carried out on young sheep spontaneously infected with gastrointestinal strongylates (48 head), Dictyocaulus filaria (42 head), Strongyloides papillosus (21 head) и Trichocephalus ovis (24 head). In each helminthiasis, the supramolecular complex of Fenbendazole was given once orally to sheep from various groups at the dose of 3,0; 2,0 and 1,0 mg a.i./kg in comparison with the base preparation Fenbendazole at the doses of 1,0 and 3,0 mg/kg. Sheep which didn’t receive the drug served as controls. The efficacy of drugs was evaluated before and 18 days after dehelmintization according to the results of coprolarvoscopic examination by flotation and G. Baermann methods. The registration of drug activity was performed using the «control test». Results and discussion: Anthelmintic efficacy was studied and a therapeutic dose for the supramolecular complex of Fenbendazole produced by chemical mechanical technology using the Drug Delivery System was determined. In gastrointestinal strongylatoses the supramolecular complex against D. filaria. at the doses of 3,0; 2,0 and 1,0 mg a.i./kg showed the efficacy of 100; 93,4 and 78% , respectively. The efficacy of supramolecular complex at the dose of 3,0 mg/kg against S. papillosus was 100 %, and against T. ovis - 98,3 % at 10–13% efficacy of the base preparation Fenbendazole at the dose of 1,0 mg/kg. The therapeutic dose for the supramolecular complex at main nematodiasis in sheep was 3,0 mg a.i./kg.